Aortic Calcification Onset and Progression: Association With the Development of Coronary Atherosclerosis. Issue 4 (April 2017) - Kälsch, Hagen; Lehmann, Nils; Moebus, Susanne; Hoffmann, Barbara; Stang, Andreas; Jöckel, Karl‐Heinz; Erbel, Raimund; Mahabadi, Amir A.
Abstract : Background: Thoracic aortic calcification (TAC) and coronary artery calcification (CAC) are markers of subclinical atherosclerosis and are associated with incident major cardiovascular events. We investigated major determinants for incidence and progression of TAC and the association between TAC and CAC incidence and progression. Methods and Results: In a population‐based cohort study, 3270 participants (aged 45–74 years, 53.1% women) received cardiac computed tomography at baseline and after a mean follow‐up of 5.1±0.3 years for quantification of calcification of the ascending (ATAC) and descending thoracic aorta (DTAC) and CAC. Multivariable relative risk regression analysis was used to investigate associations of cardiovascular risk factors with incident TAC, of baseline TAC with incident CAC, and of baseline CAC with incident TAC. Of 1243 participants with baseline TAC of 0, 517 (41.6%) revealed incident TAC after 5 years. Incidence of descending TAC was higher (34.5%) than ascending TAC (23.3%). Incident TAC after 5 years was associated with age (relative risk 1.26 [95% CI 1.21–1.33], per 5 years), blood pressure (relative risk 1.06 [95% CI 1.03–1.10], per 10 mm Hg), low‐density lipoprotein cholesterol (relative risk 1.08 [95% CI 1.04–1.12], per 20 mg/dL), and smoking (relative risk 1.28 [95% CI 1.07–1.53]). Among the 1185 participants without CAC at baseline, the risk of developing CAC was 28.3% when baseline TAC was present compared with 22.2% among those without baseline TAC (excess risk 6.1% [95% CI 1.2–11.0%]). The point estimate of excess risk for incident CAC was higher for ascending TAC (10.8% [95% CI 4.8–16.7%]) and low for descending TAC (1.8% [95% CI −3.2% to 6.7%]). Excess risk for developing ascending and descending TAC with present baseline CAC was 16.4% (95% CI 12.7–20.0%) and 15.6% (95% CI 10.8–20.4%), respectively. Conclusion: TAC and CAC share similar major determinants for incident calcification. Participants with TAC, especially ascending TAC, are at elevated risk for development of CAC.